Infective capacity of the commercial nematode Steinernema carpocapsae parasitizing Aedes aegypti mosquito larvae in Yucatán México - Ávila-López M. B.; Aguirre-Ayala D.; VidaL-Martínez V. M. (Helminthologia, 2024)
Dengue is currently the most important arbovirosis in the world, affecting over 120 countries in both tropical and sub-tropical areas, with 2500 million people at risk. Due to global warming, it is expected that Aedes aegypti will be able to survive at higher latitudes, increasing the number of people at risk. Therefore, it is crucial to develop control strategies for the mosquito to prevent its environmental impact. The objective of this paper was to determine the concentration of entomopathogenic nematode (EPN) Steinernema carpocapsae that produces the highest percentage mortality of Ae. aegypti larvae under normal environmental conditions in Yucatán (6.9 – 8.7 mg/l; temperature 25.9 – 31.5°C; pH 7.20 – 8.10). The S. carpocapsae mode of action consists of Xenorhabdus nematophila bacterial release in the haemocele insect, which produces septicaemia and consequently kills the mosquito larvae 24 – 48 h after intake. As for the methodology, a commercial EPN strain was used for experimental infection. The experimental design was a 70-h static bioassay that exposed 10 mosquito larvae per experimental unit (400-ml flask and five replicates per treatment) to four nematode concentrations (1250, 2500, 3125 and 3750 nematodes per ml) plus controls. The best treatment was with 1250 nematodes/ml, which caused 54 % mortality with respect to controls after 70 h (one-way ANOVA; F5.72, 0.05; p < 0.04). We concluded that S. carpocapsae is a promising biological control tool for killing Ae. aegypti larvae at an experimental level. However, it is still necessary to determine its performance at higher volume scales in real-life conditions.